An Analysis of Big Five Personality (OCEAN) in Linda Woolverto’s Movie Alice In Wonderland - Syamsul Bahri; Rosita Batubara; Sheikha Sri Qomaria (Education : Jurnal Sosial Humaniora dan Pendidikan, 2022)
Alice in Wonderland has been a popular movie. Many of the characters have interesting personalities like the Alice is a dependable person, Mad Hatter has erratic emotions, and the white queen is a positive human. This is an interesting phenomenon to observe. The purpose of this study is to explore the Big Five personality (OCEAN) in this movie. This study used descriptive qualitative methods to collect data, classify, identify, and analyze dialogues and monologues in the movie. As a result, this article shows that Neuroticism shows the highest level because the emotional personality is related to conflicts in the movie whose players often change emotions, while Openness to experience is at the lowest point, Alice is given a new opportunity in the movie when she kills the jabberwocky.